E-Leadership in School Management for Society 5.0: A Systematic Review from an Educational Psychology Perspective - Marwan Marwan; Saiful Bahri; Musdiani Musdiani; Syatria Adymas Pranajaya; Afif Alfiyanto (JUMPA : Jurnal Manajemen Pendidikan, 2026)
The rapid digitalization of education, accelerated by the COVID-19 pandemic and the emergence of Society 5.0, has reshaped how schools are led, yet research on electronic leadership remains fragmented between technocentric accounts of platform adoption and human-centered accounts that foreground psychological and contextual conditions, with no synthesis reading the two through an educational-psychology lens. This study aims to reconstruct how e-leadership operates in school management within the Society 5.0 era and to specify the psychological mechanisms that determine its effectiveness. Adopting a systematic literature review guided by the PRISMA 2020 protocol, the study searched the Scopus database for peer-reviewed work published between 2020 and 2025 and analyzed six included studies through thematic and framework synthesis. The findings reveal three conceptualizations of e-leadership, namely technology-facilitated, hybrid, and transformative leadership, and four psychological components that underpin its effectiveness, namely self-efficacy, motivation and engagement, social influence, and adaptability. The analysis further shows that e-leadership influences outcomes indirectly, mediated by work engagement and moderated by infrastructure, culture, crisis, professional development, and organizational climate, and it integrates these patterns into a three-layer conceptual framework centered on human well-being. The principal implication for educational management is specific: leadership development and technology policy must target the cultivation of efficacy, engagement, and resilience and align digital strategy with each institution's particular configuration, rather than treating tools and training as sufficient in themselves.